Lost Maya Cities : Archaeological Quests in the Mexican Jungle - Šprajc, Ivan (Book collections on Project MUSE., 2020)
"Previously published in Šprajc's native Slovenia and in German, this thrilling account of machete-wielding jungle expeditions has garnered enthusiastic reviews for its depictions of the efforts, dangers, successes, and disappointments experienced as the explorer-scientist searches out and documents ancient ruins that have been lost to the jungle for centuries. Also a skilled communicator and an experienced scholar, Šprajc conveys in eminently accessible prose a wealth of information on various aspects of the Mayan culture, which he has studied closely for decades. The result is a deeply personal presentation of archaeological research on one of the most enigmatic civilizations of the ancient world. Generously illustrated, this book follows the chronology of Šprajc's discoveries, focusing on what he considers the most interesting episodes. Those who specialize in Mesoamerican prehistory and archaeology will certainly relish Šprajc's reports concerning his many field surveys and the discoveries that resulted. General readers, too, will enjoy his accounts of previously undocumented sites, ancient urban centers overtaken by the jungle, massive sculpted monuments, and mysterious hieroglyphic inscriptions"--